Humas Di Lembaga Pendidikan Islam (Studi tentang Strategi Lembaga Pendidikan Islam dalam Pengembangan kehumasan di SMU 01 Muhammadiyah Gresik) - Maulidyah Amalina Rizqi; journal, journal (STIT Muhammadiyah Paciran Lamongan, 2015)
Annaba : Jurnal Pendidikan Islam Volume 2, No. 1, Maret 2016 Abstract: Education institution and society are unity which not be able to be separated, in spite of every educational activities should be suitable for community, it is mean that both education and public community have mutual understanding each other. To relate the school and public, its need special management and good public relations in the Islamic education school so there is harmony relations between the school and public to increase the school educational quality. By this way, the thesis title is relations strategy of school with public for developing the Islamic education School (case study of 01 Muhammadiyah senior high school of Gresik). The research mends to understand and explain the relations strategy of school and public for developing Islamic education School in 01 Muhammadiyah senior high school. The research uses the quality approach which was designed by case study he fill collection is done by interview technique; observation and documentation. The information election is done purposefully and be combined in snow ball sampling. To get validity and good fill so using of correct observation, triangulation and peer debriefing. Then the fill is be interactively analyzable by fill education, fill expression and conclusion. The research result explains that school and public relationship principle being run in Shalahuddin are lawfully (al `adl), discipline, wise full (al hikmah), well advice (al mau`idhah hasanah), realistic argumentation (mujadalah) and good example (uswatun hasanah). To make friendly with internal public is using of discussion between committee and teachers to grow of struggle main, giving simultaneous motivation, visiting, maximize of mosque function, ask god for helping (istighotsah), holy Qur`an studies, praying together, female activity, diba` or shalawat Nabi (greeting) to prophet, and ramadhan activity. Besides strategy and form of school and public relationship with external public are promotion, social activity (Baksos), families student meeting, study tour, theater art, sport, meeting and discussing of Al Ma`arif members, general discussion etc. and making relationship with governance. The last expression from researcher are (1) it should be made permanent human relation and not only for temporary so to be easily control and evaluation (2) effectiveness of Shalahuddin human relation to be improved time by time (3) it is needed creative thinking of new program is suitable for science and technology development, example inter net computerized etc. (4) to so the Islamic characteristic, so Shalahuddin senior high school should be having to all students especially woman for wearing Islamic performance as like using vile o cover woman body, we have known the women lady is aurat (part of body that forbidden to showed for Islam) so to cover it must be done. (5) To get more financial it should be found from another resources not only the first pay mint.